Utrata Władimira Makanina – ku hermeneutycznemu radykalizmowi - Tyczko, Krzysztof (Przestrzenie Teorii, 2019)
This article deals with radical hermeneutics in Vladimir Makanin’s micro-novel The Loss. The article presents the position that John D. Caputo’s flow is fundamental to Makanin’s hermeneutics. The author refers to Vladimir Ivancov’s research and debates with Anna Skotnicka and Anna Stankevich.